Novice Teachers’ Challenges in Implementing Hots-Oriented English Reading Instruction in a Boarding School Context - Yenni Sanruri; Dwiyani Pratiwi (FKIP - Universitas Riau, 2026)
This study focuses on examining the challenges encountered by novice teachers in implementing Higher Order Thinking Skills (HOTS)-oriented English reading instruction in an Islamic boarding school context. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis involving two novice English teachers. The findings indicate that the challenges experienced by novice teachers are multidimensional and interconnected. Pedagogical challenges include difficulties in designing HOTS-based reading questions, extending student responses through probing, managing discussion-based activities, sequencing reading tasks, and making flexible instructional decisions under time constraints. In addition, student-related challenges such as limited English proficiency and low readiness for analytical and evaluative thinking restrict students’ engagement in higher-order reading tasks. These challenges are further intensified by contextual factors within the boarding school environment, including authority-oriented classroom norms and limited instructional resources, which shape classroom interaction and encourage teacher-centered practices. Collectively, these challenges constrain the consistent implementation of HOTS-oriented English reading instruction and contribute to the dominance of lower-order cognitive practices. This study provides empirical insights into the nature of challenges faced by novice teachers, emphasizing the contextual complexity of implementing HOTS in English reading classrooms within a boarding school setting.